WordPerfect for DOS (Orem, Utah : WordPerfect, 1989)
A word-processing program which allows the user to create and format a variety of documents. Also contains holiday, business, education, and leisure packs each pack contain more than 200 images.
Production level cataloging.
Title from reference manual.
0
Keywords: MCE; Word processing